Driven to Be Good: A Stakeholder Theory Perspective on the Drivers of Corporate Social Performance - Brower, Jacob (Journal of business ethics, 2013)
Despite growing evidence of the benefits to a firm of improving corporate social performance (CSP), many firms vary significantly in terms of their CSP activities. This research investigates how the characteristics of the stakeholder landscape influence a firm’s CSP breadth. Using stakeholder theory, we specifically propose that several factors increase the salience and impact of stakeholders’ demands on the firm and that, in response to these factors, a firm’s CSP will have greater breadth. A firm’s CSP breadth is operationalized as the number of different sub-domains of CSR for which a firm has taken positive actions and is captured using a unique dataset from Kinder, Lydenburg, and Domini (KLD). This data set includes positive and negative firm actions across more than 35 different dimensions of socially responsible behavior. Findings based on a longitudinal, multi-industry sample of 447 US firms during the period from 2000 to 2007 demonstrate that firms which: (1) have greater sensitivity to stakeholder needs as a result of the firm’s strategic emphasis on marketing and/or value creation, (2) face greater diversity of stakeholder demands, and (3) encounter a greater degree of scrutiny or risk from stakeholder action have a greater breadth of CSP in response to the stakeholder landscape that they face.